Optimization of the Formulation of Sago Starch Edible Coatings Incorporated with Nano Cellulose Fiber (CNF) - Kasim, Rahmi; Bintoro, Nursigit; Rahayoe, Sri; Pranoto, Y.udi (Universiti Putra Malaysia Press, 2023)
This study aimed to produce new edible coatings based on the mixture of sago starch, cellulose nanofiber (CNF), glycerol, and tween-80.The effect of sago starch (5-10 g of starch/100 ml of distilled water), CNF (0.5-20 %), glycerol (10-30 %), and tween-80 (0.5â-10 %) based on sago starch concentration on contact angle (CA), water vapor permeability (WVP), oxygen permeability (PO2) and tensile strength (TS) properties of the edible coatings were optimized using factorial experimental design (2k).The result showed that the linear model for all independent variables was significant (P<0,05) on all responses (dependent variable).The sago starch concentration depicted a significant (p < 0.001) positive effect on contact angle; CNF showed a statistically significant effect on WVP, PO2, and TS; tween-80 showed a significant effect on all dependent variables, whereas glycerol only affected WVP. The optimum concentrations of sago starch, CNF, glycerol, and tween-80 were predicted to be 5 g/100 ml distilled water, 20 w/w, 10 w/w, and 0.5 w/w based on sago starch, respectively to obtain the minimum contact angle, WVP, PO2, and the maximum TS. The predicted data for the optimized coating formulation were in good agreement with the experimental value. This work revealed that the potential of sago starch/CNF based coating formulation could be effectively produced and successfully applied for coating of food.